Red brick dorms construction, 1960 (1960)
The North side of the Red Brick Dorms only has dirt surrounding it due to construction taking place. There are piles of dirt stacked alongside one another next to a pathway. A Galion Roll-O-Matic, which is an asphalt roller, is not in use on the side.